Perspectives of inclusive design in graphic design of Kazakhstan: The use of modern technologies - Kussebayev , Уалихан; Omirzak , Анеля (Рroblems of engineering and professional education, 2025)
The article considers the current state and development opportunities of inclusive design in the field of graphic design in Kazakhstan. The importance of creating a visual environment that is convenient for all users, including people with disabilities, is emphasized. Modern technologies - AR/VR, adaptive interfaces, tactile solutions and artificial intelligence - are described in terms of their use in inclusive design. Problems, positive experiences and specific examples in this area in Kazakhstan are presented. In addition, the social and economic benefits of an inclusive approach are analyzed. In the context of global trends, the article emphasizes the need to integrate international standards with local cultural characteristics when developing inclusive solutions in the field of graphic design. The author indicates an integrated approach - state support, education, research and active participation of the professional community - as the main condition for the development of such design. The article considers inclusive design not only as a set of technical tools, but also as an important intercultural phenomenon that ensures equality and social justice in society. The author emphasizes the need to introduce an inclusive approach into design education, as this will contribute to the formation of ethical and social responsibility of future specialists.